2020
DOI: 10.1002/star.202000139
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Resistant Starch as a Functional Food

Abstract: Dietary starches are a very important nutrient in food and are also a major source of energy with direct and specific human health contributions. They have gained great attention and been widely explored owing to their functional properties and health benefits. Resistant starch as a functional food is addressed in this study, alongside its newly discovered significance to human health. The potential sources and types of resistant starch are discussed, based on recent developments. The physiological significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 112 publications
(135 reference statements)
1
27
0
Order By: Relevance
“…Conversely, it was also reported that sprouting can induce more crystalline starch structures, which are more resistant to enzymatic hydrolysis, and thereby may increase resistant starch (Cornejo et al, 2015). Resistant starch can provide prebiotic benefits as it escapes digestion in the small intestine and is fermented by colonic bacteria (Bede & Zaixiang, 2021). Stern et al (2021) did not report any significant changes in resistant starch in wheat sprouted for 36 h whereas, Marti et al (2017) reported higher levels of slowly digestible starch in bread prepared from 100% wheat flour that was sprouted for 48 h, although research in this area is limited.…”
Section: Influence Of Sprouting On the Nutritional Composition Of Cer...mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it was also reported that sprouting can induce more crystalline starch structures, which are more resistant to enzymatic hydrolysis, and thereby may increase resistant starch (Cornejo et al, 2015). Resistant starch can provide prebiotic benefits as it escapes digestion in the small intestine and is fermented by colonic bacteria (Bede & Zaixiang, 2021). Stern et al (2021) did not report any significant changes in resistant starch in wheat sprouted for 36 h whereas, Marti et al (2017) reported higher levels of slowly digestible starch in bread prepared from 100% wheat flour that was sprouted for 48 h, although research in this area is limited.…”
Section: Influence Of Sprouting On the Nutritional Composition Of Cer...mentioning
confidence: 99%
“…Stern et al (2021) did not report any significant changes in resistant starch in wheat sprouted for 36 h whereas, Marti et al (2017) reported higher levels of slowly digestible starch in bread prepared from 100% wheat flour that was sprouted for 48 h, although research in this area is limited. The impact of sprouting on starch digestibility can depend on the time, pH and temperatures applied during soaking, sprouting and drying (Bede & Zaixiang, 2021).…”
Section: Influence Of Sprouting On the Nutritional Composition Of Cer...mentioning
confidence: 99%
“…According to the literature, pea starch is characterized by a C-type crystalline polymorph that comprises more resistant starch than the A-type polymorphs characteristic of wheat or maize. [39][40][41] This may be due to the presence of longer amylopectin chains that are able to crystallize at double helix formation, leading to an enlarged crystal lattice with greater resistance to depolymerization. 41,42 Moreover, a higher amylose content is considered to contribute to the formation of resistant starch because of the organization of long amylose chains into double helices and the high potential to retrograde during product storage.…”
Section: Papermentioning
confidence: 99%
“…It is usually hydrolyzed after 120 min, being typically fermented by colonic microbiota [ 107 , 110 ]. Resistant starches may be resistant to digestive enzymes because the compact nature of the molecules may not allow the enzymes to reach the starch granules [ 111 ]. Resistant starches contribute fewer calories than regular starch molecules during digestion in the GIT [ 106 ].…”
Section: Sweetpotato Bioactive Compounds and Their Potential Health Benefitsmentioning
confidence: 99%
“…Resistant starches contribute fewer calories than regular starch molecules during digestion in the GIT [ 106 ]. Resistant starch has similar physiological benefits to dietary fiber [ 111 ].…”
Section: Sweetpotato Bioactive Compounds and Their Potential Health Benefitsmentioning
confidence: 99%